Integrative dermatology - Norman, Robert A., 1955-; Shenefelt, Philip D.; Rupani, Reena N. ([New York] : Oxford University Press, 2014)
This title combines conventional treatment options with time tested alternative treatment options for skin disorders. By integrating the best of Western and Eastern medicine, it aims to broaden the armamentarium of clinicians treating skin diseases.
Previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 15, 2016).
Keywords: Skin -- Diseases -- Treatment; Integrative medicine